ANALYSIS OF GLOBAL ECONOMIC POLICY UNCERTAINTY, TRADE FACTORS, AND PORTFOLIO INVESTMENT FACTORS ON THE RUPIAH EXCHANGE RATE - Anggun Merlyana; Thomas Andrian; Dian Fajarini (Journal Informatic, Education and Management (JIEM), 2026)
This study analyzes the determinants of the Rupiah/US Dollar exchange rate in Indonesia during 2016–2025 using the Autoregressive Distributed Lag (ARDL) approach. The results show that Global Economic Policy Uncertainty (GEPU) and the Chinese Yuan exchange rate have a positive and significant effect on the Rupiah exchange rate in both the short and long run. Indonesia's inflation has a significant negative effect in the long run but no significant effect in the short run. Exports to China have a negative and significant effect in the short run but a positive and significant effect in the long run, whereas exports to the United States have no significant effect. Indonesia's government bond yield has a positive and significant effect only in the short run, while the US Treasury 10-year bond yield has a negative and significant effect in the short run but a positive and significant effect in the long run. The findings indicate that external factors, particularly global economic uncertainty, the Chinese Yuan exchange rate, and the US Treasury 10-year bond yield, play a more important role in influencing the Rupiah exchange rate than domestic factors.